[Ge9{M(CO)5}3]4−: electrophilic addition of M(CO)5 and [E9]4− Zintl anions (M = Cr, Mo, W). Issue 21 (9th May 2017) - Wang, Lulu; Wang, Yi; Li, Zhenyu; Ruan, Huapeng; Xu, Li
Abstract : Electrophilic addition of M(CO)5 and [E9 ] n − at the three capping sites was achieved by the nucleophilic substitution reactions of K4 Ge9 and M(CO)6, which produced the novel C 3h -[Ge9 {M(CO)5 }3 ] 4− (M = Cr, 1 ; Mo, 2 ; W, 3 ) exhibiting a perfect tricapped trigonal prismatic core structure. Abstract : Nucleophilic substitution reactions of K4 Ge9 and M(CO)6 produced [Ge9 {M(CO)5 }3 ] 4− (M = Cr, 1a ; Mo, 2a ; W, 3a ). The electrophilic addition of M(CO)5 and [Ge9 ] 4− occurred at the three capping sites to form almost perfect tricapped trigonal prismatic1a–3a with crystallographic C 3h symmetry.